Wage and labor productivity in manufacturing industry of Malaysia - Yusoff, Mohammed (2016)
Malaysia has been undergoing the process of industrialization of its economy to achieve the goal as a developed and high income nation by 2020. Labor productivity plays an important role in economic development because higher labor productivity results in higher level of income per capita and higher standard of living. But labor productivity in Malaysia is relatively low compared to the newly developed nations such as Singapore and Taiwan. Malaysia has been focusing on education, gross domestic investment and foreign direct investment to improve labor productivity and enhance the process of industrialization to make Malaysian exports more competitive in the world market. Thus, the main objective of this study is to examine the link between wage rate and labor productivity in the manufacturing sector of Malaysia. We use the three digit Malaysian standard industrial classification data of the manufacturing sector of Malaysia and estimate the model. We test for the presence of heteroskedaticity and found that the errors are homoskedastic and therefore the model can be efficiently estimated using the pooled OLS. The results of this study support the hypothesis that there is a close relationship between labor productivity and wage rates in the manufacturing sector in Malaysia at firm level. A 1% increase in labor productivity will increase wage rate by only 0.6% suggesting that manufacturing firms in Malaysia pay the wages and salaries to their workers in accordance with the workers’ productivity, albeit not in full amount.